2021
DOI: 10.3390/antiox10071074
|View full text |Cite
|
Sign up to set email alerts
|

The Anxiolytic and Antidepressant Effects of Diallyl Disulfide and GYY4137 in Animals with Chronic Neuropathic Pain

Abstract: When neuropathic pain is maintained long term, it can also lead to the development of emotional disorders that are even more intense than pain perception and difficult to treat. Hydrogen sulfide (H2S) donors relieve chronic pain, but their effects on the associated mood disorders are not completely elucidated. We evaluated if treatment with DADS (diallyl disulfide) or GYY4137 (morpholin-4-ium 4-methoxyphenyl(morpholino) phosphinodithioate dichloromethane complex), two slow-releasing H2S donors, inhibits the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 65 publications
12
33
0
Order By: Relevance
“…In the first set of experiments, the antinociceptive effects produced by the acute administration of different doses of DADS (25–200 µmols/kg), P-ITC (18.6–29 µmols/kg), or vehicle at 10 days after CFA-injection were evaluated ( n = 6 animals per dose). Mice were tested at 1 h after DADS or P-ITC injection in accordance with our previous studies [ 8 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first set of experiments, the antinociceptive effects produced by the acute administration of different doses of DADS (25–200 µmols/kg), P-ITC (18.6–29 µmols/kg), or vehicle at 10 days after CFA-injection were evaluated ( n = 6 animals per dose). Mice were tested at 1 h after DADS or P-ITC injection in accordance with our previous studies [ 8 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this context, recent studies proved that the exogenous administration of slow-releasing H 2 S donors, such as phenyl isothiocyanate (P-ITC) or allyl isothiocyanate (A-ITC), attenuated osteoarthritis and neuropathic pain, thus turning these compounds into potential therapeutical targets for the treatment of inflammatory pain [ 6 , 7 , 8 ]. Other investigations also demonstrated the antinociceptive effects of other slow-releasing H 2 S compounds, such as diallyl disulfide (DADS) and morpholin-4-ium 4-methoxyphenyl (morpholino) phosphinodithioate dichloromethane complex (GYY4137), in models of osteoarthritis or nerve injury-induced neuropathic pain [ 9 , 10 ]. These and other studies further revealed that the possible mechanisms involved in H 2 S-mediated antinociceptive actions in nociceptive, osteoarthritis, and neuropathic pain might be produced by opening the voltage-gated potassium channels, such as the Kv7 [ 6 , 7 , 10 ] and the ATP-sensitive (KATP) potassium channels [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first experiments, we evaluated the effects of repetitive intraperitoneal administration, twice daily, of 200 µmol/kg of DADS and 32 µmol/kg of GYY4137, over 3 and 4 consecutive days, on the cognitive and grip strength losses and mechanical allodynia caused by osteoarthritis (n = 6-8 animals for each group). The doses of DADS and GYY4137 were chosen in conformity with another research [47]. The effects of the same treatments on associated depressive-and anxiety-like behaviors were further assessed (n = 8 animals for each group).…”
Section: Methodsmentioning
confidence: 99%
“…DADS and GYY4137 were purchased from Sigma-Aldrich (St. Louis, MO, USA) and dissolved in SS. Both drugs were intraperitoneally administered 1 h before testing, in a final volume of 10 mL/kg, in accordance with our previous pilot studies and other work [47]. Both drugs were prepared before use, and for each group treated with a drug, the respective control group received the same volume of corresponding vehicle.…”
Section: Drugsmentioning
confidence: 99%